THE RELATIONSHIP BETWEEN INFORMATION TECHNOLOGY AND ORGANIZATIONAL CULTURE IN THE UNIVERSITY LIBRARIES OF SINDH, PAKISTAN. - Rahoo, Liaquat Ali; Channar, Paras Bashir; Abbasi, Arshad Mahmood; Ahmed, Tanveer; Khan, Muhammad Ali (The journal of contemporary issues in business and government, 2021)
This study aimed to investigate the relationship between use of ICT and organizational culture in University libraries of Sindh, Pakistan. The research is descriptive and correlation. Populations of study library professionals who are working in university libraries and the sample sizes to 330 stratified random sampling method was selected instruments consisted of the questionnaire researchers'' organizational cultures based on the characteristics of the seven Robbins and questionnaire-based information, and communication technology skills are the seven ICDL. Reliability using Cronbach''s alpha for organizational culture, 09 / 9 and 68 /9determined the validity of ICT. To analyze the questions and review questions in addition to descriptive statistics, t-test with two independent samples, chip-square test and Pearson correlation coefficient was used.